Virtual reality exposure using three-dimensional images for the treatment of social phobia - Gebara,Cristiane M. (2016)
Objective: To test a potential treatment for social phobia, which provides exposure to phobia-inducing situations via computer-generated, three-dimensional images, using an open clinical trial design. Methods: Twenty-one patients with a DSM-IV diagnosis of social phobia took part in the trial. Treatment consisted of up to 12 sessions of exposure to relevant images, each session lasting 50 minutes. Results: Improvements in social anxiety were seen in all scales and instruments used, including at follow-up 6 months after the end of treatment. The average number of sessions was seven, as the participants habituated rapidly to the process. Only one participant dropped out. Conclusion: This study provides evidence that exposure to computer-generated three-dimensional images is relatively inexpensive, leads to greater treatment adherence, and can reduce social anxiety. Further studies are needed to corroborate these findings.